Strategi Pengembangan Objek Wisata Istana Maimun Sebagai Pusat Pariwisata Sejarah Di Kota Medan - Booni Tauhid; Robert Deffie; Handoko (Politeknik Pariwisata Medan, 2022)
Historically the development of Medan since the beginning has positioned itself into a trading center city. Medan as the capital of the Land Deli which then became the capital of North Sumatra Province, made ​​the city is growing more rapidly. In the construction of Medan city, there are five of the most prominent actors: government, private (business), Community, Professional, and Intellectual. Similarly, in economic activities, in addition to well known public sector played by the Government is also important private and public sectors. Revenue (PAD) is a picture of the financial potential of the region that rely on elements of regional taxes and levies. With regard to revenue from the sector of the local levy can explore the potential of natural resources in the form of tourist attraction. It is recognized that the tourism sector is not the developer and the largest contributor to the sector but has the potential to increase local revenues. The method used in this study is quantitative and qualitative approaches. The variables of this study are the factors driving and inhibiting the development as a tourist attraction Maimoon Palace History Tourism Center in Medan